Exploring Eigth-Grade Students’ Mathematical Literacy in PISA-Adapted Space and Shape Problem at Levels 3-5 - Dwi Arisma Wahyudi; Sufyani Prabawanto; Al Jupri (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2026)
This study explores the mathematical literacy profiles of 30 eighth-grade students in Bandung Barat Regency, focusing on their abilities during the formulating stage of PISA-adapted geometry tasks across Levels 3, 4, and 5. Utilizing a qualitative descriptive-exploratory design, data were collected through a Mathematical Literacy Test (MLT) focusing on rectangular area and perimeter alongside task-based clinical interviews. Student responses were mapped using a specialized representational action coding scheme (R1–R7). The empirical findings reveal a critical negative trend: as task complexity escalates, successful mathematical formulation plummets, leaving over 80% of students trapped in either absolute cognitive paralysis or unscientific guessing at Levels 4 and 5. Specifically, non-response status (R7) reached 46.67% at Level 4 due to severe reading literacy barriers and working memory overload under dense linguistic contexts. Meanwhile, subjective intuition (R6) was the most dominant pattern, affecting 50% of the cohort at Level 5, driven by a profound epistemological fragmentation where real-world scenarios are treated as isolated from formal mathematics. Dysfunctional visual scaffolding (R4) and rigid procedural dependencies (R3) further stalled progression. These systemic failures at the upstream formulating stage ultimately blocked students from reaching the employing or interpreting phases.